Analysis of Development Priorities for the Leading Pepper Commodity in East Lampung Regency Using the Analytical Hierarchy Process (AHP) Approach - Sari, Novia Ambar; Ivan’s, Eny; Indaryati, Sri (Manajemen Agribisnis: Jurnal Agribisnis, 2026)
The agricultural sector serves as the primary economic driver of East Lampung Regency, with black pepper (Lampung Black Pepper) acting as a leading export-oriented plantation commodity. However, the existence of this commodity faces a continuous decline in productivity caused by pest infestations, plant diseases, and economic pressures from plunging farm-gate prices. This study aims to analyze the priority ranking of pepper farming constraints and formulate strategic policy interventions for its development. Utilizing a mixed qualitative-quantitative approach through the Analytic Hierarchy Process (AHP) method, primary data were gathered from seven expert respondents selected via expert sampling. The geometric mean synthesis of group questionnaire data yielded valid results with a Consistency Ratio below the maximum threshold ($CR < 0.10$). Criteria weighting revealed that the selling price of pepper is the most critical constraint (weight 0.342). Nevertheless, at the tactical level, experts prioritized improved cultivation practices and integrated pest management (IPM) as the highest policy strategy (weight 0.358), integrated with market access expansion through formal partnership schemes (weight 0.245). Revitalizing black pepper requires a harmonious governance synergy between upstream scientific assistance and downstream price stability assurance.